Analysis of Fiscal and Monetary Policies on Investment and Capital Markets in Indonesia - Mohammad Fakhri Al-Farabi; Mohammad Wisnu Fajar; Liza tazkiyatin ni'mah (Department of Islamic Economics, Faculty of Islamic Economics and Business, Universitas Islam Negeri Sunan Kalijaga, 2024)
Government investment is important to increase the rate of economic growth. Many benefits will be achieved if the investment made by the government is successful. From this discussion, we are interested in discussing government investment. The research method you use is qualitative with a regression analysis method to analyze the relationship between fiscal and monetary policy with investment and the capital market. The result of the discussion is that infrastructure investment is the most relevant thing that the government can invest in, because this investment is useful for encouraging economic growth, improving the quality of life, attracting private investment, can create jobs, and is the government's own responsibility for the development and welfare of the people.